Using Modeling The Way Strategy in Fiqh Learning to Improve Student's Understanding Of MIT Jabal Nur - Munjaji, Irfan; Rahayu S, Putri; Zubaidi, Zubaidi (AT-TURATS, 2024)
Learning strategies play a crucial role in achieving effective educational outcomes. At MIT Jabal Nur, in Tangerang City, the implementation of the Modeling The Way strategy in Fiqh lessons successfully improved students' understanding of the material, especially the chapter on Hajj. This success is supported by the principal's policy of giving teachers the freedom to choose the most appropriate teaching methods, as well as the active role of teachers in encouraging students to participate in the learning process through demonstrations and simulations. As a result, students showed significant improvement in motivation, involvement, and understanding of the material taught. This study uses a qualitative method with a case study approach to explore the implementation of Modeling The Way and its impact on students' understanding at MIT Jabal Nur. The results from interviews and observations show that this strategy not only increased student engagement in learning but also helped develop their skills in collaboration and initiative. In addition, support from the community, teachers, and parents also contributed to creating a conducive learning environment. Overall, the implementation of Modeling The Way at MIT Jabal Nur, Tangerang City, has successfully improved the quality of Fiqh education, making it an effective teaching model to be applied to other subjects. This strategy also emphasizes the importance of a supportive school environment and positive interaction between teachers and students in achieving educational goals.Strategi pembelajaran sangat penting untuk mencapai hasil pendidikan yang efektif. Di MIT Jabal Nur, Kota Tangerang, penerapan strategi Modeling The Way dalam pembelajaran Fikih berhasil meningkatkan pemahaman siswa, terutama dalam materi bab Haji. Keberhasilan ini didukung oleh kebijakan kepala sekolah yang memberi kebebasan kepada guru untuk memilih metode pembelajaran yang paling tepat, serta peran aktif guru dalam mendorong siswa untuk berpartisipasi melalui demonstrasi dan simulasi. Hasilnya, siswa menunjukkan peningkatan yang signifikan dalam motivasi, keterlibatan, dan pemahaman materi yang diajarkan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus untuk mengkaji penerapan Modeling The Way dan dampaknya terhadap pemahaman siswa di MIT Jabal Nur. Hasil wawancara dan observasi menunjukkan bahwa strategi ini tidak hanya meningkatkan keterlibatan siswa dalam pembelajaran, tetapi juga membantu mengembangkan keterampilan mereka dalam berkolaborasi dan berinisiatif. Selain itu, dukungan dari masyarakat, guru, dan orang tua juga berperan penting dalam menciptakan lingkungan pembelajaran yang mendukung. Secara keseluruhan, penerapan Modeling The Way di MIT Jabal Nur, Kota Tangerang, berhasil meningkatkan kualitas pendidikan Fikih, menjadikannya model pengajaran yang efektif untuk mata pelajaran lainnya. Strategi ini juga menekankan pentingnya lingkungan sekolah yang mendukung dan interaksi positif antara guru dan siswa dalam mencapai tujuan pendidikan.